Contrasting the grain boundary-affected performance of zinc and indium oxide transparent conductors - Vai, A; Rashidi, N; Fang, Y; Kuznetsov, V; Edwards, P (IOP Publishing, 2016)
Zinc oxide-based transparent conductors have long been advanced for their potential as low-cost, earth-abundant replacements for the indium oxide-based materials that currently dominate in practical applications. However, this potential has yet to be realized because of the difficulties in producing zinc oxide thin films with the necessary high levels of electrical conductivity and environmental stability that are readily achieved using indium oxide. To better understand the fundamental reasons for this, polycrystalline zinc and indium oxide thin films were prepared across a range of deposition temperatures using the technique of spray pyrolysis. Electrical transport measurements of these samples both as a function of temperature and UV irradiation were correlated with film morphology to illustrate that the different grain boundary behaviour of these two materials is one of the key reasons for their divergent performance. This is a critical challenge that must be addressed before any substantial increase in the adoption of ZnO-based transparent conductors can take place.